Comprehensive Utilization Technology of Aronia melanocarpa - Dongfang Shi; Jing Xu; Li Sheng; Kai Song (Molecules, 2024)
Aronia melanocarpa fruit contains a variety of active ingredients, such as phenolic acids, anthocyanins, proanthocyanidins, etc. Relevant in vivo and in vitro studies have concluded that it has beneficial effects in terms of treating dyslipidemia, hypertension, glucose metabolism disorders, etc. This article discusses the nutritional value and food processing of Aronia melanocarpa and reviews the chemical components of Aronia melanocarpa and the pharmacological activities of related substances in order to summarize the chemical characteristics of the fruit and its development prospects. The process optimization of juice production, the impact of antioxidant capacity, and the comprehensive utilization of pomace in feed are discussed. This article provides a reference for future comprehensive application research and product development of Aronia melanocarpa.